The Influence of Green Investment, Environmental Disclosure, and Good Corporate Governance on the Financial Performance of Mining Companies in Indonesia - Uul Ukhudiah; Zaenal Arifin (LP2M IAIN Palopo, 2026)
This study aims to analyze the influence of Green Investment and Environmental Disclosure and Good Corporate Governance on the financial performance of companies as measured using Return on Asset (ROA) and Return on Shares in mining companies listed on the Indonesia Stock Exchange during the period 2019-2024. The background of this research is based on the increasing attention to sustainability and environmental management issues in the mining sector which has a significant impact on the environment and has the potential to affect the company's financial performance. This study uses a quantitative approach with a panel data regression analysis method. The research sample consisted of 21 companies obtained through purposive sampling techniques with data sourced from annual financial statements, company sustainability reports and OWN ratings. The results of the study show that Green Investment does not have a significant effect on the company's financial performance, both as measured by Return on Asset (ROA) and Return on Shares. Environmental Disclosure has a positive and significant effect on ROA, but does not have a significant effect on Stock Return. Meanwhile, Good Corporate Governance did not show a significant influence on ROA or Share Return. These findings indicate that sustainability and corporate governance practices have more impact on a company's internal financial performance than on the capital market response in the short term, particularly in the mining sector.